EFFECTIVENESS OF A SCHOOL-BASED MULTICOMPONENT INTERVENTION ON CHILDREN NUTRITIONAL STATUS AMONG PRIMARY SCHOOL CHILDREN IN BANGKOK, THAILAND - Chawla, Nattapon; Panza, Alessio; Sirikulchayanonta, Chutima; Kumar, Ramesh; Taneepanichskul, Surasak (Journal of Ayub Medical College Abbottabad, 2017)
Background: Childhood obesity has become a major public health issue today. The prevalence of obesity and overweight is increasing in both adult and children. Childhood obesity in Thailand has more than doubled since the 1960s and a recent study reported that overweight and obesity in Thai is the 5th highest in Asia. The present study objective is to evaluate the effectiveness of a life skills multicomponent school-based intervention on children’s nutritional status. Methods: A quasi-experimental design was conducted in two-groups (control and intervention schools) on 453 students attending grade levels 4-5 in Bangkok. Two schools were selected for control, and two schools for intervention groups. The intervention included education, dietary, physical activity, food-environment, school built-environment, and life skills components. Outcomes were measured at baseline and post-treatment measured after 6 months. Results: The intervention group had significant improvements in healthier practice (+1.5 mean difference, p=0.048) on dietary habits and physical activity, lowered cholesterol levels (-2.43 mean, p=0.019), and higher HDL levels (+4.06 p=0.028) as compared to control. A higher reduction of overweight individuals among the intervention group over the intervention period was observed. Physical activity and consumption of vegetable increased while consumption of high-caloric snacks and fasts food decreased in children after the intervention. Conclusion: Childhood overweight and obesity is a serious public health problem based on its increasing rates and the associated health risks. This study indicated that multidisciplinary approach on school-based interventions is likely most effective to prevent children becoming overweight in long term. More research should be conducted on school-based intervention with longer intervention periods with higher sustainability. Keywords: Obesity; Life skills; Multicomponent; Physical activity; Cholesterol; HDL